Large group face recognition for attendance tracking - Yeap, Jia Hao (Nanyang Technological University, 2024)
Large group facial recognition for attendance taking has a very practical application use case in today’s academic institutions. With the multitude of modern state-of-the-art models being developed, this project will serve to evaluate the feasibility of large group facial recognition for attendance taking, using selected modern models.